Mutation Screening and Functional Study of SLC26A4 in Chinese Patients with Congenital Hypothyroidism - Chang-Run Zhang; Yuan-Ping Shi; Cao-Xu Zhang; Feng Sun; Wen-Jiao Zhu; Rui-Jia Zhang; Ya Fang; Qian-Yue Zhang; Chen-Yan Yan; Ying-Xia Ying; Shuang-Xia Zhao; Huai-Dong Song (Galenos Yayincilik, 2022)
INTRODUCTION: Defects in the human solute carrier family 26 member 4 (SLC26A4) gene are reported to be one of the causes of congenital hypothyroidism (CH). We aimed to identify SLC26A4 mutations in Chinese patients with CH and analyze the function of the mutations. METHODS: Patients with primary CH were screened for 21 CH candidate genes mutations by targeted next-generation sequencing. All the exons and exon-intron boundaries of SLC26A4 were identified and analyzed. The function of six missense mutation in SLC26A4 were further investigated in vitro. RESULTS: Among 273 patients with CH, seven distinct SLC26A4 heterozygous mutations (p.S49R, p.I363L, p.R409H, p.T485M, p.D661E, p.H723R, c.919-2A>G) were identified in 10 patients (3.66%, 10/273). In vitro experiments showed that mutation p.I363L, p.R409H, p.H723R affect the membrane location and ion transport of SLC26A4, while p.S49R did not. Mutation p.T485M and p.D661E only affected ion transport, but had no effect on the membrane location. DISCUSSION AND CONCLUSION: The prevalence of SLC26A4 mutations was 3.66% in Chinese patients with CH. Five mutations (p.I363L, p.R409H, p.T485M, p.D661E and p.H723R) impaired the membrane location or ion transport function of SLC26A4, suggesting important roles for Ile363, Arg409, Thr485, Asp661, and His723 residues in SLC26A4 function. As all variants identified were heterozygous, the pathogenesis of these patients cannot be explained, and the pathogenesis of these patients needs further study